Análise comparativa dos custos de internações hospitalares de idosos, pelo SUS, em municípios com diferentes realidades de renda média domiciliar per capita - Kummer, Simone Stochero (2014)
The growing population aging has led to several changes in the needs of the society where we live, requiring a better understanding on topics ranging from epidemiological transition to financial issues related to how to defray the expenses of this longevity. It is known that changes in age structure and the consequences of population aging increase the prevalence of chronic degenerative diseases, a process that leads to an increase in costs for health systems. The main purpose of this study was to associate costs of elderly hospitalizations with mean per capita household income in elderly's municipality of residence. The method was a cross-sectional study that assessed hospitalizations of elderly people living in the municipalities of Alvorada, Ivoti and Porto Alegre, Southern Brazil, and admitted at hospitals in the state of Rio Grande do Sul in 2011, based on data collected from SIH/SUS-DATASUS, a database created by the Brazilian Ministry of Health. These municipalities were selected for this study because they showed the greatest disparity in mean per capita household income among the municipalities belonging to their Regional Health Department. Using the tabulation tool named TABWIN, the following analysis parameters were selected: total number, frequency and length of hospitalizations. Such data were associated with socioeconomic and demographic data of the municipalities under study. Considering the overall amount of hospitalizations of elderly people living in the three municipalities analyzed, it was observed that inhabitants of Porto Alegre showed the lowest frequency of hospitalizations (11.15%), whereas their hospitalizations had the highest mean cost (1.896,19 BRL [Brazilian reais]). Inhabitants of Ivoti showed the highest frequency of hospitalizations (18.53%), with the lowest mean cost (R$ 1,001.10 BRL), whereas inhabitants of Alvorada had an intermediate frequency of hospitalizations (16.57%), with a mean cost of R$ 1,483.66 BRL. As for the association between healthcare costs and mean household income, Porto Alegre showed the highest income (1,722.37 BRL) and the highest per capita gross internal product (GDP), Ivoti had intermediate income (1,019.75 BRL) and per capita GDP, and Alvorada presented a significantly lower income (587.84 BRL). However, although Porto Alegre showed the highest per capita cost with hospitalization of its inhabitants (31.78 BRL), it assigned only 0.1% of its GDP to cover these expenses, whereas Alvorada had a per capita cost of 22.08 BRL, assigning 0.29% of its per capita GDP, and Ivoti showed the lower cost per capita (18.94 BRL) for covering elderly hospitalizations and also the lowest portion of its GDP per capita for this purpose (0.08%). The combination of demographic, socioeconomic, epidemiological, and morbidity and mortality data provides a more solid, critical and endorsed view for the construction of favorable or unfavorable opinions regarding health actions and the use of public resources. Additionally, it is important to develop data analysis and collection skills among health professionals and managers, in order to potentiate care so that it meets the actual needs of each municipality or region during decision making processes.